2022
DOI: 10.1002/jnr.25118
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of functional recovery in a larval zebrafish model of spinal cord injury

Abstract: Human spinal cord injury (SCI) is characterized by permanent loss of damaged axons, resulting in chronic disability. In contrast, zebrafish can regenerate axonal projections following central nervous system injury and re-establish synaptic contacts with distant targets; elucidation of the underlying molecular events is an important goal with translational potential for improving outcomes in SCI patients. We generated transgenic zebrafish with GFP-labeled axons and transected their spinal cords at 10 days post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Gait analysis offers a scalable approach to quantify swim quality. Prior applications of gait analysis, such as dorsal centerline posture and tail beat kinematics, supported the model that functional recovery emerges directly from structural recovery among ray-finned fishes (12, 17, 18). These studies revealed stepwise recovery of specific gait features in correlation with axon regeneration from V2a interneurons (12, 19).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Gait analysis offers a scalable approach to quantify swim quality. Prior applications of gait analysis, such as dorsal centerline posture and tail beat kinematics, supported the model that functional recovery emerges directly from structural recovery among ray-finned fishes (12, 17, 18). These studies revealed stepwise recovery of specific gait features in correlation with axon regeneration from V2a interneurons (12, 19).…”
Section: Introductionmentioning
confidence: 94%
“…One viable option includes novelty detection, which classifies behavior episodes as inliers or outliers relative to a control distribution. Another option is posture parameter quantification, which has been used in larval zebrafish (17). Examples of posture parameter quantification from human and mouse studies used behavior and gait features, such as quantified response to stimulus and range or speed of motion, to measure functional recovery (33, 34, 35, 36).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although new quality measurements have been developed for larval fish including body angle (Zeng et al, 2021), power spectral densities (Vasudevan et al, 2021), and centerline posture kinematics (Hossainian et al, 2022), published quality measurements for adult fish are limited to manual scoring of perceived swim ability (Becker et al, 1997;Goldshmit et al, 2012;Strand et al, 2016), tail beat frequency and amplitude (Huang et al, 2022). Moreover, manually assigned scores are subjective and do not scale well for higher throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic development is classically defined as ending at the time of hatching, 3-4 days post fertilization (dpf) (Kimmel et al, 1995;Parichy et al, 2009) with larval development continuing for approximately six weeks. Often laboratories use late embryonic and early larval stages due to ease and ethical considerations (Tsarouchas et al, 2018) with some studies looking at larvae as old as 10 dpf (Hossainian et al, 2022). Furthermore, neurogenesis of primary motor neurons is greatly reduced at 2 dpf (Reimer et al, 2013) and nascent myelin is observed 3-4 dpf (Bin and Lyons, 2016;Kirby et al, 2006;Park et al, 2002;Preston and Macklin, 2015).…”
Section: Introductionmentioning
confidence: 99%